Los micromamíferos (Eulipotyphla, Chiroptera, Rodentia y Lagomorpha) del yacimiento del Pleistoceno Superior de la cueva de El Sidrón (Asturias) - Sesé, C.; De La Rasilla, M.; Duarte Matías, E. (Zenodo, 2018)
(Uploaded by Plazi for the Bat Literature Project) In the Late Pleistocene site of El Sidrón cave, with a date of ~ 49,000 ky, known for its numerous fossil remains of Neanderthals, some remains of micromammals were found, whose detailed study is carried out in this work. The determined faunal association is the following: Sorex araneus–Sorex coronatus, Neomys cf. fodiens, Talpa sp., Rhinolophus euryale-Rhinolophus mehelyi, Marmota cf. marmota, Eliomys quercinus, Glis glis, Arvicola terrestris, Chionomys nivalis, Microtus arvalis-Microtus agrestis, Microtus lusitanicus, Microtus oeconomus, Clethrionomys glareolus, Apodemus sylvaticus-Apodemus flavicollis and Oryctolagus cuniculus. These taxa are present in the current fauna of Asturias and Cantabrian Region except for Microtus oeconomus that disappeared from the Iberian Peninsula in historical times and is currently in northernmost Eurasian regions. The fauna of micromammals as a whole seems to indicate a predominantly open space environment, generally of certain moisture meadows and vegetation development at ground level, although there would also be wooded areas of some entity and some watercourse. The presence, although with few remains, of some thermophilic species, and the absence of cold climate indicator species, seem to indicate that the climate during the formation of the fossiliferous deposits would be relatively temperate and humid, probably similar to the current one in the area.